KONSEP WANITA SHALIHAH DALAM KISAH ISTRI FIR’AUN (ANALISIS AL-QUR’AN SURAT AT-TAHRIM AYAT 11) - Wiji Susanto (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2019)
The Qur'an consists mainly of three main points, namely monotheism, Islamic laws, and the stories of previous people. The Asiyah story is a story of the previous people and one of the stories that needs to be an example for Muslims. With her determination she maintained her faith in a palace full of paganism. this is interesting to study because the name Asiyah is not mentioned directly, only written by the wife of Fir’aun. Besides that, in her prayer contained in the letter at-Tahrim verse 11, which contains the value of faith. Whereas to be a woman of righteousness is none other than having faith in order to be obedient and obey to religion. The concept of shalihah women in Islam is a woman who is submissive and obedient to her religion, which is always closer and pious to Allah. The pious attitude possessed by a shalihah woman can give birth to an act or behavior that is in accordance with moral values. Based on the results of the study it can be concluded that the concept of shalihah women in the story of Fir’aun's wife based on the at-Tahrim verse verse: 11 is a woman who has a high firmness of faith, never complained (sincerely with the provisions of Allah SWT), always worshiped to Allah SWT, has great patience, having great thinking, strong personality, being able to distinguish between truth and error, asking for protection and salvation only from Allah SWT.